2024
DOI: 10.1371/journal.pone.0295514
|View full text |Cite
|
Sign up to set email alerts
|

Determining online consumer’s luxury purchase intention: The influence of antecedent factors and the moderating role of brand awareness, perceived risk, and web atmospherics

Muhammad Ussama Majeed,
Hira Aftab,
Ali Arslan
et al.

Abstract: The Internet has become the fastest-growing way to sell luxury products. Purchase intention for luxury products in online stores has taken attention in the last few years since the sector has proliferated. The primary objective of this study is to examine the impact of various factors such as Product knowledge, Price consciousness, Perceived enjoyment, Perceived ease of usage, and usefulness on online luxury purchase intention in developing countries like Pakistan. Data was collected from 267 luxury fashion cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Over the past decade significant changes have been observed in Pakistan's Climate due to environmental degradation, impacting health and socio-economic well-being. Research indicates that while increased environmental awareness promotes green products, actual purchasing behavior may not always align with intentions (Majeed et al, 2024). Studies have shown conflicting results on the relationship between consumer attitude and purchase intention (Soomro et al, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the past decade significant changes have been observed in Pakistan's Climate due to environmental degradation, impacting health and socio-economic well-being. Research indicates that while increased environmental awareness promotes green products, actual purchasing behavior may not always align with intentions (Majeed et al, 2024). Studies have shown conflicting results on the relationship between consumer attitude and purchase intention (Soomro et al, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
“…The study suggests integrating consumer behavior factors into future research to assess actual environmental concerns and responsibility. Majeed et al (2024), found that environmental concerns negatively impact the pricing and social status of consumers who buy green products in Pakistan. It further suggested the need to explore environmental concerns and purchase as contributors.…”
Section: Research Gapmentioning
confidence: 99%
See 3 more Smart Citations